Coronavirus Disease 2019 (COVID-19) Mitigation Efforts and Testing During an In-Person Training Event—Uganda, 12–29 October 2020. (29th April 2021) - Laws, Rebecca L; Biraro, Sam; Kirungi, Wilford; Gianetti, Brittany; Aibo, Dorothy; Awor, Anna C; West, Christine; Sachathep, Karampreet K; Kiyingi, Herbert; Ward, Jennifer; Mwangi, Christina; Nkurunziza, Peter; et al.
Abstract: Large public-health training events may result in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) transmission. Universal SARS-CoV-2 testing during trainings for the Uganda Population-based HIV Impact Assessment identified 28 of 475 (5.9%) individuals with coronavirus disease 2019 (COVID-19) among attendees; most (89.3%) were asymptomatic. Until COVID-19 vaccine is readily available for staff and participants, effective COVID-19 mitigation measures, along with SARS-CoV-2 testing, are recommended for in-person trainings, particularly when trainees will have subsequent contact with survey participants.